Rancang Bangun Aplikasi Medical Representative Berbasis Web Pada PT. Lapi Laboratories Jakarta Selatan - Heri Heryanto (Jurnal Komputer dan Informatika, 2024)
The development of pharmacy is interesting to discuss because its products are one of the basic needs. Medicine is one of the healing factors for health problems. Health is one of the keys to the survival of society. Medical Representative is part of the pharmaceutical industry which is also an important component in its company. Medical Representative has the task of conveying benefits to doctors and medical personnel. Medical Representative as the spearhead of a company that specifically sells drugs, they must be able to market their products well and consistently, namely by using a direct or face-to-face communication marketing strategy between Medical Representative as the seller, and the doctor as the user. In this study I created a special application for the needs of a websitebased Medical Representative using the php framework and MySQL as its database, with this application, it is expected to be able to help Medical Representative officers in providing information about products or drugs offered to consumers, in this case Doctors, this study was conducted at PT LAPI Laboratories South Jakarta